2011
DOI: 10.1038/cdd.2011.150
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin NUP153 guards genome integrity by promoting nuclear import of 53BP1

Abstract: 53BP1 is a mediator of DNA damage response (DDR) and a tumor suppressor whose accumulation on damaged chromatin promotes DNA repair and enhances DDR signaling. Using foci formation of 53BP1 as a readout in two human cell lines, we performed an siRNA-based functional high-content microscopy screen for modulators of cellular response to ionizing radiation (IR). Here, we provide the complete results of this screen as an information resource, and validate and functionally characterize one of the identified 'hits':… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 45 publications
4
59
1
Order By: Relevance
“…Several studies reported the screening of genes in regulating the recruitment of 53BP1 to DNA damage sites (38)(39)(40). Depletion of UbcH7 was reported to increase the size of 53BP1 foci (30), similar to our observation.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies reported the screening of genes in regulating the recruitment of 53BP1 to DNA damage sites (38)(39)(40). Depletion of UbcH7 was reported to increase the size of 53BP1 foci (30), similar to our observation.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, previous work showed that depletion of NUP153 leads to import impairment of selective proteins. 16 Moreover, while we were conducting this study, Moudry et al 17 confirmed the mislocalization of 53BP1 in NUP153 depleted cells and showed the requirement of NUP153 for 53BP1 nuclear import.…”
Section: Resultssupporting
confidence: 64%
“…In this context, it has been shown that Nup153 mediates the nuclear import of the DNA repair mediator 53BP1 (also known as TP53BP1), regulating the nonhomologous end joining (NHEJ) pathway of DNA double-strand break (DSB) repair (Cobb et al, 2016;Lemaitre et al, 2012;Moudry et al, 2011). Nup50 appears to be required for the nuclear import of XRCC1, which plays roles in single-strand break and base excision repair (Kirby et al, 2015).…”
Section: Introductionmentioning
confidence: 99%